2013
DOI: 10.3892/ijo.2013.2000
|View full text |Cite
|
Sign up to set email alerts
|

Mucin-like peptides from Echinococcus granulosus induce antitumor activity

Abstract: There is substantial evidence suggesting that certain parasites can have antitumor properties. We evaluated mucin peptides derived from the helminth Echinococcus granulosus (denominated Egmuc) as potential inducers of antitumor activity. We present data showing that Egmuc peptides were capable of inducing an increase of activated NK cells in the spleen of immunized mice, a fact that was correlated with the capacity of splenocytes to mediate killing of tumor cells. We demonstrated that Egmuc peptides enhance LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 51 publications
0
23
0
2
Order By: Relevance
“…7 We have recently found that immunization with mucin peptides derived from the helminth parasite Echinococcus granulosus can potently induce antitumor activity by increasing the frequency of activated NK cells and endowing splenocytes with the capacity to mediate killing of tumor cells. 10 In addition, we observed that vaccination with E. granulosus antigens (human hydatic cyst fluid) significantly inhibits colon cancer growth (both in prophylatictic and therapeutic settings) via induction of antitumor immunity. 11 Interestingly, mice immunized with hydatic cyst fluid developed specific antibodies capable of recognizing tumor cells, 11 consistent with previous reports indicating that parasites and cancer cells share common antigens.…”
Section: (Conicet) Buenos Aires Argentinamentioning
confidence: 95%
See 1 more Smart Citation
“…7 We have recently found that immunization with mucin peptides derived from the helminth parasite Echinococcus granulosus can potently induce antitumor activity by increasing the frequency of activated NK cells and endowing splenocytes with the capacity to mediate killing of tumor cells. 10 In addition, we observed that vaccination with E. granulosus antigens (human hydatic cyst fluid) significantly inhibits colon cancer growth (both in prophylatictic and therapeutic settings) via induction of antitumor immunity. 11 Interestingly, mice immunized with hydatic cyst fluid developed specific antibodies capable of recognizing tumor cells, 11 consistent with previous reports indicating that parasites and cancer cells share common antigens.…”
Section: (Conicet) Buenos Aires Argentinamentioning
confidence: 95%
“…Moreover, it was also found that malaria infection suppresses Lewis lung cancer growth via induction of innate and specific adaptive antitumor responses characterized by heightened production of Th1‐type cytokines . We have recently found that immunization with mucin peptides derived from the helminth parasite Echinococcus granulosus can potently induce antitumor activity by increasing the frequency of activated NK cells and endowing splenocytes with the capacity to mediate killing of tumor cells . In addition, we observed that vaccination with E. granulosus antigens (human hydatic cyst fluid) significantly inhibits colon cancer growth (both in prophylatictic and therapeutic settings) via induction of antitumor immunity .…”
mentioning
confidence: 96%
“…Noya et al (2014) ½Q14 also demonstrated that mucinlike peptides from E. granulosus induce antitumour activity. In studies on the identification and characterization of Emp53, the homologue of human tumour suppressor p53, from E. multilocularis, Cheng et al (2015) concluded that since the parasite develops in host organs, it must have evolved a stress defence system, which could involve Emp53, to cope with various genotoxic and cellular stresses that may cause DNA damage and genomic instability.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 96%
“…Indeed, O‐glycosylated Tn antigens produced by E. granulosus are highly found in the sera of the patients with hydatid disease . In addition, mucin‐like peptides from E. granulosus can augment nonspecific natural killer (NK) cell activity and expression of cytokines that are involved in antitumour immune responses . Thus, the pre‐existing immune mediators against E. granulosus Tn antigens can cross‐react and may initiate immunity against transformed cells.…”
mentioning
confidence: 99%